Unveiling the Gender Gap : Investigating the Impact of GRIT and Learning Motivation on Economic Learning Achievement Among High School Students - Anggraeni, Dina; Wardani, Dewi Kusuma; Noviani, Leny (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to analyze the impact of GRIT and Motivation to learn on student achievement in economic subjects and to assess the role of gender as a moderating variable. This study used a survey method with a quantitative approach. The population in this study were grade X students in Purworejo Regency, Cluster random sampling obtained a sample of 142 students data collection techniques using questionnaires and tests. Data were analyzed using the IBM SPSS Version 25 application with hypothesis testing and the Moderated Regression Analysis (MRA) test. The results showed a significant impact of GRIT and learning motivation on learning achievement (Ã¢= 0.267, t-count = 2.864, p = 0.005), (Ã¢= 0.288, t-count = 3.092, p = 0.002). Furthermore, gender as a moderating variable can moderate and strengthen the impact of GRIT and learning motivation on learning achievement. The novelty of this study was the existence of GRIT variables tested on students (especially economics students), while other studies used Grit on employees and teachers. The results of this research could contribute to shaping the behavior of students with high strength, resilience, and motivation during economics learning to maximize the resulting learning achievement.